Transitivity Process on Song Lyrics in Ariana Grande's Album 'thank u, next' - Vivi Novalia Sitinjak; Gihon Kusy Marpaung; Ella Meidelin Kokardi; Novelia; Susanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
People listen to music a lot nowadays due to the emotional connections it creates. Moreover, music, especially songs, can be a convenient and enjoyable form of entertainment and expression in people's daily lives. This study focused on one of the subdiscipline of discourse analysis, namely transitivity. The analysis of transitivity in this study is using the theory of Halliday & Matthiessen (2014) that transitivity process consists of 6 processes: material process, mental process, relational process, behavioral process, verbal process and existential process. The source of data is based on Ariana Grandeâ€™s album â€œthank u, nextâ€ and taking its song lyrics to be explored. The study results show that the material process consists of ninety-nine clauses; the mental process consists of two hundred forty-one clauses; the relational process consists of fifty-one clauses; the behavioral process consists of seventy-five clauses; the verbal process consist of forty-one clauses; and the existential process consist of two clauses. So, it can be concluded the total clauses existing in this album are five hundred and eight clauses.